2D automated SEM and 3D X-ray computed tomography study on inclusion analysis of steels. (2nd January 2020) - Bandi, Bharath; Santillana, Begona; Tiekink, Wouter; Koura, Nadia; Williams, Mark; Srirangam, Prakash
ABSTRACT: In this research work, inclusion analysis was done on titanium micro-alloyed low carbon steels using automated scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM/EDS), and 3D X-ray computed tomography (XCT) techniques. Automated SEM/EDS analysis provided the information about the average size, number, shape, and the composition of the inclusions. The inclusions are categorized as calcium aluminates, titanium nitrides, and 'other' inclusions with an average size of 1.66, 1.52, and 1.31 µm, respectively. To estimate the actual amount of inclusions present and to understand their 3D morphologies, XCT analysis was done at two different resolutions of 1.8 µm and 590 nm. The employment of these resolutions enabled the technique to detect huge number of inclusions with a wide size range from 0.75 to 201.4 µm. Moreover, the XCT technique revealed the presence of complex irregular shaped inclusions. Effective combination of these two techniques for inclusion analysis gives complete quantified information about the inclusions present in steels.